2005
DOI: 10.1073/pnas.0505300102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Cyclin D1 abrogates genesis of rhabdoid tumors resulting from Ini1 loss

Abstract: Rhabdoid tumors are aggressive pediatric malignancies for which, currently, there are no effective or standard treatment strategies. Rhabdoid tumors arise because of the loss of the tumor suppressor gene INI1. We have previously demonstrated that INI1 represses Cyclin D1 transcription in rhabdoid cells by directly recruiting histone deacetylase 1 complex to its promoter, leading to G 0-G1 arrest. Expression of Cyclin D1 overcomes cell cycle arrest mediated by INI1 and Cyclin D1 overexpression in human rhabdoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 34 publications
4
82
1
1
Order By: Relevance
“…Similar to MRTs cell lines (7,10), flavopiridol treatment in VAESBJ induced both CCND1 protein downmodulation and cell-cycle arrest. Unexpectedly, we observed a synergistic effect on cell-cycle block with combined Flavopiridol treatment and SMARCB1 ectopic reexpression, indicating that flavopiridol affects cell proliferation and viability through pathways at least in part independent of SMARCB1 tumor suppressor.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to MRTs cell lines (7,10), flavopiridol treatment in VAESBJ induced both CCND1 protein downmodulation and cell-cycle arrest. Unexpectedly, we observed a synergistic effect on cell-cycle block with combined Flavopiridol treatment and SMARCB1 ectopic reexpression, indicating that flavopiridol affects cell proliferation and viability through pathways at least in part independent of SMARCB1 tumor suppressor.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, in MRT cell lines, it has been shown that SMARCB1 loss is associated with responsiveness to Cdk/cyclin inhibitors, such as 4-HPR (7) and flavopiridol (8). In addition, the in vivo spontaneous tumorigenesis in SMARCB1 þ/À knockout mice is increased by TP53-null genetic background (9) and is prevented by CCND1 ablation (10), further supporting the interaction with crucial molecules controlling cell-cycle progression.…”
Section: Introductionmentioning
confidence: 81%
“…Cyclin D1 is derepressed in human and mouse INI1À/À RTs (Zhang et al, 2002;Tsikitis et al, 2005). In addition, genetic ablation of cyclin D1 is sufficient to abrogate the genesis of RTs in vivo mouse models (Tsikitis et al, 2005). These studies suggest that RTs are critically dependent on the presence of cyclin D1 for genesis and/or survival.…”
Section: Introductionmentioning
confidence: 76%
“…Effect of cyclin D1 siRNA on proliferation of rhabdoid cells Mouse knockout studies indicated that deletion of cyclin D1 abrogates the genesis of RTs (Tsikitis et al, 2005). To test if cyclin D1 itself is required for the survival of RT cell lines, we transfected a rhabdoid cell line with small interfering RNA oligonucleotides against cyclin D1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation